miR-155 mediated regulation of PKG1 and its implications on cell invasion, migration, and apoptosis in preeclampsia through NF-κB pathway - Xiaohua Luo; Xiaopei Guo; Ningning Chen; Rui Peng; Ci Pan; Zhuyin Li; Bing Zhao; Ruonan Ji; Siyu Li (Biology Direct)
Abstract Background Preeclampsia (PE) is a severe pregnancy complication characterized by complex molecular interactions. Understanding these interactions is crucial for developing effective therapeutic strategies. Methods This study applies a pharmacometabolomics approach to explore the roles of miR-155 and PKG1 in PE, focusing on the regulatory influence of the NF-κB signaling pathway. Blood metabolomic profiles were analyzed, and bioinformatics tools, IHC staining, Western blot (WB) analysis, and immunofluorescence (IF) localization were employed to determine the expression and function of miR-155 and PKG1. Cell invasion, migration, proliferation, and apoptosis assays were conducted to assess miR-155’s modulation of PKG1. Additionally, RT-qPCR and WB analysis elucidated NF-κB-mediated regulation mechanisms. Results Our findings indicate significant metabolic alterations associated with miR-155 modulation of PKG1, with NF-κB acting as a critical upstream regulator. The study demonstrates that miR-155 affects cellular functions such as invasion, migration, proliferation, and apoptosis through PKG1 modulation. Furthermore, the NF-κB signaling pathway regulates miR-155 expression, contributing to the pathological processes of PE. Conclusion This study provides a proof of concept for using pharmacometabolomics to understand the molecular mechanisms of PE, suggesting new therapeutic targets and advancing personalized medicine approaches. These insights highlight the potential of pharmacometabolomics to complement genomic and transcriptional data in disease characterization and treatment strategies, offering new avenues for therapeutic intervention in PE.